The Influence of Training, and Motivation, on Teacher Performance Mediated by Reward Penabur Christian Elementary School Gading Serpong - Rocki Parmonangan (PT. Anagata Sembagi Education, 2024)
In the world of education, educators or teachers play a very important role. Teachers are the main implementers of teaching and learning activities in the school environment. To achieve optimal results, teachers must be supported by quality human resources. One of the critical factors in building superior human resources in education is teacher performance. Teacher performance is reflected in the thoughts and efforts given in carrying out their duties as teachers. Improving the quality of teachers contributes significantly to increasing the productivity and effectiveness of the education process in schools. In particular, at Penabur Gading Serpong Christian Elementary School (SDK), teachers play a central role in the effort to build a better quality education. The success of this school is due to the role of teachers as implementers of teaching and learning activities. Despite mastering various subjects, without the support of quality human resources, teachers cannot achieve optimal results. This study aims to determine the effect of training, motivation on employee or teacher performance mediated by rewards. Located at SDK Penabur Gading Serpong, totaling 70 (Seventy) people and all members of the population as well as the sample so that this research is census research. The results of this analysis show that all indicators used in this study are valid and reliable. This study uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. This study provides evidence of a positive and significant effect